Divine Contradiction: some snippets - Beall, Jeffrey C. (Religious studies, 2024)
Two doctrines (or axioms) of christian theology sharply distinguish christian monotheism from its traditional monotheistic siblings (viz. jewish and islamic monotheism): the incarnation of God and the triunity of God. Both doctrines, as many have long observed, face a conspicuous so-called logical problem - namely, apparent contradiction. How should the strong appearance of such fundamental contradiction be explained? Beall's answer: the incarnation and trinity appear to be contradictory because God is a contradictory being - a being of whom some contradictions are true. The full truth of God is expressed only via contradiction, which is why the fundamental axioms of christian theology have long appeared to be contradictory. Divine Contradiction presents the target contradictory account of the trinity; its predecessor The Contradictory Christ presents the contradictory account of the incarnation.